LATE PUNIC OR EARLY ROMAN? - Sáez Romero, Antonio M.; Luaces, Max; Moreno Pulido, Elena (Herom: Journal on Hellenistic & Roman Material Culture, 2016)
The article examines the Torre Alta pottery workshop in Cadiz, Spain to demonstrate the suitability of applying certain widespread-terms in the Mediterranean historiography such as Neo-Punic or Late Punic and the gradual processes of cultural change of the site to Early Roman.